Cybersecurity issues in Cellular Technology - Mahajan, Gaurav (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
This whitepaper aims to provide an in-depth analysis of implementing Zero Trust solution with cellular devices with different solution vendors available today. It covers the fundamental principles of Zero Trust, its relevance to SIM security, and the importance of Zero trust Cellular solutions. Additionally, it addresses the benefits and challenges associated with this integration.